Exploring University ESP Teachers’ Beliefs about Course Evaluation - Jerković, Jelena M.; Vidaković, Mirna M. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
The paper examines tertiary English for Specific Purposes (ESP) teachers’ experiences and perceptions of course evaluation within a contemporary theoretical framework. It aims to determine the evaluation impetus, identify gaps in the dissemination of evaluation results, provide insight into teachers’ beliefs about their evaluation competencies and needs, and address their concerns and suggestions for the evaluation process. The study was motivated by the expanding influence of ESP courses, criticism of current evaluation practices initiated by universities, and lack of research in the field. The purpose was to deepen understanding of the evaluation process among teachers and other relevant parties and to obtain teachers’ recommendations for enhancing the evaluation capacity of the above-mentioned groups, which ultimately contributes to educational excellence and student success. The sample comprised 43 ESP teachers from private and state institutions of higher education in Serbia, who completed an electronic questionnaire. The quantitative data were analyzed using descriptive statistics, while thematic content analysis was employed for the qualitative data. The results indicate that course evaluation is still not fully accepted as a regular procedure at the tertiary level in Serbia, since not all institutions initiate it and there is an obvious gap in communication of the results. Yet, teachers generally consider evaluation an essential component of an ESP course and require training opportunities for broadening their knowledge and developing the skills relevant for the effective administration of course evaluation. The pedagogical implications of the study underscore the necessity of teachers’ professional development, the alignment of evaluation procedures with pedagogical realities, and the enhancement of cooperation with institutions and other relevant stakeholders.
Keywords: course evaluation; English for Specific Purposes; tertiary evaluation practice; teachers’ evaluation competencies